Pengembangan Media Nearpod Berbasis Problem Based Learning pada Materi Energi Terbarukan - Hadi, Wulandari; Buhungo, Trisnawaty Junus; Samatowa , Lukman (Universitas Pendidikan Mandalika, 2025)
Physics learning requires active student engagement and strong conceptual understanding, particularly for topics related to real-life phenomena such as renewable energy. However, classroom instruction remains largely conventional and has yet to fully utilize interactive technologies. To address this issue, a Nearpod-based learning medium integrated with the Problem-Based Learning (PBL) model was developed as a solution to enhance student engagement, activeness, and conceptual comprehension. This study employed a Research and Development (R&D) approach using the ASSURE instructional design model, which includes six stages: analyzing learner characteristics, stating learning objectives, selecting methods and media, utilizing media and materials, requiring learner participation, and conducting evaluation and revision. The participants were tenth-grade students from SMA Negeri 1 Kabila. Research instruments included expert validation sheets for content and media, student activity observation sheets, student response questionnaires, and learning outcome tests (pre-test and post-test). The results showed that the Nearpod media was categorized as highly feasible, with validation scores from content and media experts exceeding the established eligibility standards. Regarding practicality, all indicators of instructional implementation during both sessions reached 100%, indicating that every step of the PBL learning syntax was executed effectively. Student activity observations revealed high engagement levels, ranging from 64% to 100%, while student responses were highly positive in terms of visual design, ease of use, and interactivity. In terms of effectiveness, all students achieved post-test scores above the school’s Minimum Mastery Criteria (KKTP), showing a significant improvement compared to the pre-test results. These findings demonstrate that the Nearpod media successfully increases student engagement, facilitates interactive learning, and supports better understanding of renewable energy concepts through a problem-based approach.